2020
DOI: 10.18280/acsm.440502
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Matrix Hybrid Membranes Polyvinylidene Fluoride/Polyvinylpyrrolidone/Silica Gel/Zinc Oxide for Cr(VI) Removal from Water

Abstract: Matrix hybrid membranes, based on polyvinylidene fluoride (PVDF), poly (N-vinylpyrrolidone) (PVP), silica gel (SG) and zinc oxide (ZnO) were synthesized by phase inversion via immersion precipitation method. The characterization of membrane samples was performed using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), optical microscopy, contact angle, porosity, mean pore size and water permeability measurements. The FTIR analysis showed the appearance of new bands attributed to the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…The composition of the synthetic solutions based on PVDF, PVP, Sodium maghnite and DMF is shown in Table 3, the components was mixed at 8 h with temperature of 50℃, one uses the method of precipitation by phase inversion [1]. 2.5 Characterization of membranes 2.5.1 Fourier transformed infrared spectroscopy (FTIR) of the membrane samples After drying the samples of each membrane at a temperature of 50℃.…”
Section: Membranes Synthesis Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The composition of the synthetic solutions based on PVDF, PVP, Sodium maghnite and DMF is shown in Table 3, the components was mixed at 8 h with temperature of 50℃, one uses the method of precipitation by phase inversion [1]. 2.5 Characterization of membranes 2.5.1 Fourier transformed infrared spectroscopy (FTIR) of the membrane samples After drying the samples of each membrane at a temperature of 50℃.…”
Section: Membranes Synthesis Methodsmentioning
confidence: 99%
“…It was found that the peaks located at 10°,17° and 20° belongs to (001), (110) symmetrical planes respectively. The XRD data collected from Table 1 show that these planes reflect the positions of the atoms corresponding to α crystal conformation of the PVDF in M1 membrane [1]. The peak located at 20.26° is assigned to the planes (022) of βcrystal phase of PVDF (Table 1).…”
Section: Xrd Patterns Analysismentioning
confidence: 98%
See 3 more Smart Citations